Seismic Velocity Structure of Upper Mantle Beneath the Oldest Pacific Seafloor: Insights From Finite‐Frequency Tomography - Hyunsun Kang; YoungHee Kim; Shu‐Huei Hung; Pei‐Ying Patty Lin; Takehi Isse; Hitoshi Kawakatsu; Sang‐Mook Lee; Hisashi Utada; Nozomu Takeuchi; Hajime Shiobara; Hiroko Sugioka; Seung‐Sep Kim (Geochemistry, Geophysics, Geosystems, 2023)
Abstract The oldest oceanic basin (160–180 Ma) in the western Pacific is the birthplace of the Pacific Plate and is thus essential for understanding the formation and evolution of the oceanic plate. However, the upper mantle structure beneath the region has not been thoroughly investigated because of the remoteness and difficulties of long‐term in situ seismic measurements at the ocean bottom. From 2018 to 2019, the Oldest‐1 experiment on the oldest seafloor was conducted as part of the international Pacific Array initiative. We present the first three‐dimensional P‐wave velocity structure down to a depth of 350 km based on the relative travel time residuals of teleseismic earthquakes recorded by 11 broadband ocean‐bottom seismometers operated during the Oldest‐1 experiment. Our result shows a fast P‐wave velocity anomaly (VP perturbation of 2%–4% faster than average) at a depth of 95–185 km beneath the northeast of the study area. This structure is interpreted as evidence of dry, viscous, and rigid materials at depths below the lithosphere. Two slow anomalies (VP perturbation of 2%–4% slower than average) are seen beneath the southwestern and eastern (the oldest seafloor >170 Ma) parts of the array site. The low‐velocity zones are found at depths of 95–305 km. The observed velocity structures can be indicative of plume activities that affected the upper mantle as the Pacific Plate migrated over hotspots from the southeast. Alternatively, the observed velocity features may provide seismic evidence for small‐scale sublithospheric convection.